The Incidental Vocabulary Learning Opportunities in the Reading Comprehension Passages - Kuni Hikmah Hidayati (IAIN Kendari, 2021)
This paper reports on research into vocabulary learning opportunities provided in the reading comprehension passages. It is a quantitative study with a corpus analysis using AntWordProfiler program. Data was collected from reading comprehension passages involving all words in the passages. The results show that the reading comprehension passages provided a great opportunity to deepen knowledge of first 1,000 most frequent words. However, they did not provide good opportunities to develop knowledge of second 1,000 most frequent words, academic words and unlisted words well. This is because most of the word families found in the reading comprehension passages occurred once and less than five times. In conclusion, the reading comprehension passages provided opportunities to learn first 1,000 most frequent words and lacked the opportunities for second 1,000 most frequent words, academic words and unlisted words.